The effect of excessive disodium ethylene diamine tetraacetic acid (Na2EDTA) anticoagulant concentration on leukocytes profile in peripheral blood examination (Medical Journal of Indonesia, 2007)
Accuracy of leukocytes profile assessment is influenced by several pre analytical factors, among others, the anticoagulant concentration. EDTA is one of the most frequently used anticoagulant in peripheral blood examination. Several references stated that inappropriate concentration of EDTA anticoagulant in blood sample may affect the result of leukocytes profile in peripheral blood examination. The aim of this study was to evaluate whether there are differences among leukocytes profile in peripheral blood examination specimens, which were prepared with excessive Na2EDTA anticoagulant in different concentration. This study was conducted in Faculty of Medicine, Gadjah Mada University. Blood samples from 30 subjects were taken using vein puncture. Two millimeters blood was divided into 4 Na2EDTA-containing tubes. Before that, one drop of blood without Na2EDTA anticoagulant was used to make blood film right after vein puncture, as control. Each tubes contained different concentration of anticoagulant. The first tube contained Na2EDTA in standard concentration 2 mg/ml; the remaining tubes contained 4 mg/ml, 6 mg/ml, and 8 mg/ml respectively. These samples were immediately examined using SYSMEX SE-9500 automatic cell counter to measure the total and differential leukocytes count; and were stained with Wright staining for morphological examination under the microscope. These procedures were done before 20 minutes of vein puncture. There were significant decrement of total leukocytes count, absolute differential leukocytes count and monocyte percentage following excessive Na2EDTA administration. Neutrophil percentage was found to be relatively increased and the difference was significant. Lymphocyte, eosinophil and basophil percentages were not significantly different. Morphological examination showed significant increment in irregular cytoplasm margin, vacoulation and irregular nuclei lobes following excessive Na2EDTA administration. It is concluded that excessive concentration of Na2EDTA used in blood specimen preparation, will lead to changes in leukocytes profile as the concentration increased. Standard Na2EDTA anticoagulant concentration did not alter any leukocytes count and morphology, except for irregular cytoplasm margin and irregular nuclei lobes. (Med J Indones 2007; 16:168-75)